Penerapan Media Bahan Ajar Flipbook Berbasis Problem Based Learning (PBL) dalam Upaya Peningkatan Keterampilan Menulis Kalimat Fakta dan Opini pada Siswa Kelas VI SD Bintara Jaya - Munawaroh, Siti; Putri Prilin, Roofisyha Anggel; Nugraha, Rakhaprima Karima; Purwati, Panca Dewi (YASIN, 2025)
Although the use of digital media in primary school instruction has received considerable attention in previous studies, research that specifically examines the integration of flipbooks with Problem Based Learning (PBL) to improve the ability to write factual and opinion sentences remains limited. This study aimed to evaluate the effectiveness of PBL-based flipbook teaching materials in improving the writing skills of sixth-grade students, particularly in distinguishing between facts and opinions. A mixed-methods approach was employed using a one-group pretest–posttest design combined with qualitative observations and interviews, involving 22 students selected through purposive sampling. Data were collected using writing tests, observation sheets, student response questionnaires, and interview protocols, and were analyzed using descriptive statistics and thematic analysis. The findings show that the integration of flipbooks and PBL increased student engagement, strengthened group collaboration, and improved individual learning outcomes, although variation in achievement remained. These results contribute to the development of digital constructivist learning theory and broaden understanding of the use of interactive media in Indonesian language instruction. The study concludes that interactive flipbooks play an important role in supporting elementary school students’ analytical writing skills and recommends that teachers adopt digital PBL-based teaching materials to strengthen literacy competencies. The implications of this research include theoretical contributions to digital pedagogy and practical recommendations for educators to modernize learning resources, while also opening opportunities for further exploration of adaptive digital media and differentiated instruction in the teaching of writing.